ASEAN TIGERS’ TRILEMMA: A TRAVEL AND TOURISM BATTLE IN COMPETITIVENESS AND RESPONSIVENESS - Tomasowa, Judith Marilyn (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Tarumanagara, 2017)
ASEAN is facing a trilemma in travel and tourisme competitiveness and responsiveness which is shown in 2015 Travel & Tourism Competitiveness Index (TTCI) by World Economic Forum.The ranks of ASEAN member are so differs due to ASEAN members weakness and strength. By having considered that ASEAN’s goals are to establish a strong economic community and to improve regional autonomy, development, competitiveness, to cope with poverty, human development and equality, then they should work out these issues, which are also as the focuss in ASEAN 2016-2025Tourism Strategic Plan. ASEAN should think as One Vision, One Identity and One Community, in any discussion or agreement to come out with the best solutions. It is demanded that the members and its public-private sectors to sacrifice some of its domestic and bilateral advantages, in order to gain ASEAN Regional competitive and responsive advantages to the global market demands. This paper is using qualitative method, which is supported by indexing and weighted average towards ASEAN 2015-2016 TTCI 14 pillar. It is utilizing the trend of global travellers and international visitors arrivals in ASEAN. Its results are 4 levels of priority for ASEAN Travel and Tourisme Development, discovering the needs to socializing One Identity, One Vision, One Identity and One Community at the ASEAN national levels, recommendations in Intra-ASEAN and Interregional cooperations. The paper’s purpose is present the competitiveness and responsiveness concepts and its problems that related to ASEAN trilemma that involves strategic policies and regional paradigm in.travel and tourism synergized national policies and regulations.Keywords: Tourism, Competitiveness, Sustainability, ASEAN Regional Strategy, Responsiveness.